Ambiguity and Conflict in the Implementation of Policies for Determining Traditional Villages in Siak Regency - Rizan Hasbullah; Febri Yuliani; Hasim As'ari (Department of Public Administration, 2022)
Traditional village is an original structure that has original rights in the form of rights including managing the territory and life of its customary law community. In order to realize the vision of Siak Regency to increase the existence of Malay culture in Siak Regency as the basis of identity in Siak society, and with the motto of Siak Regency